Effects of goal orientation and perceived value of toughness on antisocial behavior in soccer: The mediating role of moral disengagement - Boardley, I. D.; Kavussanu, M. (Journal of Sport & Exercise Psychology, 2010)
In this study, we examined (a) the effects of goal orientations and perceived value of toughness on antisocial behavior toward opponents and teammates in soccer and (b) whether any effects were mediated by moral disengagement. Male soccer players (N = 307) completed questionnaires assessing the aforementioned variables. Structural equation modeling indicated that ego orientation had positive and task orientation had negative direct effects on antisocial behavior toward opponents. Further, ego orientation and perceived value of toughness had indirect positive effects on antisocial behavior toward opponents and teammates which were mediated by moral disengagement. Collectively, these findings aid our understanding of the effects of personal influences on antisocial behavior and of psychosocial mechanisms that could facilitate such antisocial conduct in male soccer players.